The Market for Forward Contracts on Oil in Iceland. An assessment of market activity - Sigurður Ágúst Jakobsson 1991- (2014)
The aim of this thesis is to make an assessment of the Icelandic market for forward oil contracts and answer a few questions about its state as of the year 2014. The market is compared to the spot market, important participants are examined, other oil price risk management tools and techniques in use are named, and factors determining market size are explored. Important findings include the fact that forward contracts with oil products underlying are used by Icelandic parties, including airline and oil distribution companies. Due to a lack of information available about the volume of forward contracts in use it is not possible to estimate the size of the market, yet evidence suggests that spot market transactions are the dominant method in use for physical transactions with oil products. Other risk management tools, such as swaps, options and surcharges, are also in use by Icelandic parties, and they offer important alternatives to the use of forward contracts.